First results of instantaneous GPS/Galileo/COMPASS attitude determination - Nadarajah, Nandakumaran; Teunissen, Peter; Buist, P.; Steigenberger, P. (2012)
The advent of modernized and new global navigation satellite systems (GNSS) has enhanced the availability of satellite based positioning, navigation, and timing (PNT) solutions. Specifically, it increases redundancy and yields operational back-up or independence in case of failure or unavailability of one system. Among existing GNSS, the Chinese COMPASS navigation satellite system (CNSS) and the European Galileo system are being developed. In this contribution, a COMPASS/Galileo/GPS robustness analysis is carried out for instantaneous, unaided attitude determination. Precise attitude determination using multiple GNSS antennas mounted on a platform relies on the successful resolution of the integer carrier phase ambiguities. The constrained Least-squares AMBiguity Decorrelation Adjustment (C-LAMBDA) method has been developed for the quadratically constrained GNSS compass model that incorporates the known baseline length. In this contribution the method is used to analyse the attitude determination performance when using the GPS, the Galileo, and COMPASS systems. The attitude determination performance is evaluated using GPS/Galileo/COMPASS data sets from a real data campaign in Australia. The study includes the performance analyses of both stand-alone and mixed constellation (GPS/Galileo/COMPASS) attitude estimation under satellite outage. We demonstrate and quantify the improved availability, reliability, and accuracy of attitude determination using the combined constellation. © 2012 IEEE.